Odpowiedzi

2010-02-20T12:42:19+01:00
A) 3(x+1)= 2x
3x+3=2x
3x-2x=-3
x=-3

b) 5(z-2)= 7(1-z)
5z-10=7-7z
5z+7z=7+10
12z=17 | / 12
z=17/12
z=1 5/12

c) 2(x+4)-6= 3(x-2)+7x
2x+8-6=3x-6+7x
2x+2=10x-6
2x-10x=-6-2
-8x=-8 | /(-8)
x=1

d) 3(y+1)+6y= -2(y-1)+8
3y+3+6y= -2y+2+8
9y+3= -2y+10
9y+2y=10-3
11y=7 | /11
y=7/11
31 3 31
2010-02-20T12:42:38+01:00
A) 3(x+1)= 2x
3x+3 = 2x
3x-2x = -3
x = -3

b) 5(z-2)= 7(1-z)
5z-10 = 7-7z
5z+7z = 7+10
12z = 17 / 12
z = ¹⁷/₁₂
z = 1 ⁵/₁₂

c) 2(x+4)-6= 3(x-2)+7x
2x+8 - 6 = 3x-6 +7x
2x-3x-7x = -6-8+6
-8x = -8 / :(-8)
x = 1

d) 3(y+1)+6y= -2(y-1)+8
3y +3 + 6y = -2y +2 +8
3y + 6y + 2y = 2+8-3
11y = 7 / : 11
y= ⁷/₁₁
19 4 19